Case report: Bordetella holmesii: A rare pathogen causing infective endocarditis associated glomerulonephritis - Gavcovich, Tara; Al Barbandi, Malek; Millan, Pamela; Isner, Elizabeth; Defreitas, Marissa J.; Glaberson, Wendy; Katsoufis, Chryso P.; Chandar, Jayanthi; Sigurjonsdottir, Vaka; Gonzalez, Ivan A.; Swaminathan, Sethuraman; Zuo, Yiqin; et al. (Frontiers in Pediatrics, 2023)
Infective endocarditis can cause multiorgan dysfunction and chronic kidney disease, in addition to cardiac sequelae. The presentation may be vague and can manifest as acute glomerulonephritis. While the most common pathogens of infective endocarditis are Staphylococcus and Streptococcus species, we report a rare pathogen Bordetella holmesii causing infective endocarditis associated glomerulonephritis. A 20-year-old male with tetralogy of Fallot with pulmonary atresia and aortopulmonary collaterals underwent several cardiac surgeries including prosthetic pulmonary valve replacement in the past. He was admitted for 3 days at an outside hospital for fever, cough and hemoptysis, diagnosed with streptococcal pharyngitis, for which he receievd antibiotics. Five weeks later, he presented to our institution with lower extremity edema and gross hematuria. On exam, he was afebrile, normotensive, had a 7-kg weight gain with anasarca, and a systolic murmur, without rash. Investigations revealed elevated serum creatinine, nephrotic range proteinuria, hematuria, and hypocomplementemia, consistent with acute glomerulonephritis. Given his cardiac history, blood cultures were collected from 3 sites. Broad-spectrum antibiotics were initiated when he subsequently developed fever. Renal pathology on biopsy showed diffuse proliferative immune complex-mediated glomerulonephritis. Transesophageal echocardiogram visualized a vegetation on the pulmonary valve. Bordetella holmesii was ultimately cultured from the prior and current hospitalization. A serum sample detecting microbial cell-free DNA sequencing confirmed Bordetella holmesii at very high levels. After completing 6 weeks of intravenous antibiotics with concurrent angiotensin receptor blockade, his kidney function recovered with improvement in hypocomplementemia and proteinuria. This case report highlights the early recognition and comprehensive evaluation of a rare organism causing IE associated GN, which allowed for renal recovery and preserved cardiac function.